Eugenio Gudin versus Roberto Simonsen: desenvolvimentismo, neoliberalismo e a construção do Brasil durante o Século XX (1940-70) - Tolentino Neto, Leovigildo Melgaço (2016)
The debate on industrialization is bound to a classic controversy within the economy, which gained momentum during the twentieth century: planning and interventionism on the one hand, versus the free market on the other. This research seeks to rekindle the debate on industrialization taking focused the classic discussion of economic planning, which occurred in the 1940s during the Vargas government, between Eugenio Gudin and Roberto Simonsen. The goal is to expose as thought exposed by the authors were crucial in building the economic development of Brazil between the decades of 1940-1970. The research used historical-relativistic method to review the original text of the debate, on behalf of the Latin American context under which it was unleashed. The relativistic analysis calls for extensive research nature, that is, leaning to the historical and social context in which occur the design ideas. Relativists are researchers who nurture interests in the relations of the history of economic thought with the author's own intellectual framework in question. Relativists, contrary to orthodox Schumpeterian, are researchers who nurture interests in the relations of the history of economic thought with the author's own intellectual framework in question. The results of the research show that the ideas defended by Simonsen were the drivers of development in Brazil over the study period, giving the basis for the building of the main development plans of the national economy: Plan Goals, PAEG, I PND II PND and the creation of BNDE.